Experimental investigation on hydrodynamic forces of semi-submerged cylinders in combined steady flow and oscillatory flow. (15th January 2023) - Hu, Tengyan; Ren, Haojie; Shen, Jiawei; Niu, Zhibo; Zhang, Mengmeng; Xu, Yuwang; Song, Bin; Sun, Tongxiao
Abstract: Hydrodynamic forces on a semi-submerged cylinder are experimentally investigated under the combination of steady and oscillatory flow. The hydrodynamic force in the in-line (IL) and cross-flow (CF) directions under combined flow with and without overtopping are respectively observed in detail. Then, the feasibility and validity of the force models in both IL and CF directions are further verified for the non-overtopping and overtopping regions. The modified Morison equation is then proposed by changing the flow velocity squared term to the higher-order index term. Through the least square method (LSM), the best fitting index and hydrodynamic coefficients, including the drag coefficients, added mass coefficients, and lift coefficients, are identified and summarized. The independency of the fitting index and hydrodynamic coefficients with Keulegan-Carpenter (KC) numbers has been witnessed. The empirical models for predicting hydrodynamic coefficients under the non-overtopping and overtopping flow states in combined flow are developed based on the experimental observation. The overtopping occurrence is proposed to be determined by the total Froude number. With these contributions, the present work provides a promising method to calculate the hydrodynamic force on a semi-submerged cylinder in unsteady flow. Highlights: The drag force is no longer proportional to the square of the relative velocity when overtopping occurs in combined flow. The Morison equation is modified to be the applicant for semi-submerged cylinders when overtopping occurs in combined flow. The independence of the coefficients with KC number was witnessed in combined flow. The total Froude number is proposed to determine the hydrodynamic coefficients, higher-order index and overtopping occurrence. The promising empirical models of the hydrodynamic coefficients in combined flow are developed.